Mind‐body interventions for fear of cancer recurrence: A systematic review and meta‐analysis. Issue 11 (5th June 2018) - Hall, Daniel L.; Luberto, Christina M.; Philpotts, Lisa L.; Song, Rhayun; Park, Elyse R.; Yeh, Gloria Y.
Abstract: Objective: Fear of cancer recurrence (FCR) is a common existential concern and source of distress among adults with a cancer history. Multiple randomized controlled trials (RCTs) have examined mind‐body approaches to mitigating FCR. We summarized characteristics of these trials and calculated their pooled effects on decreasing FCR. Methods: Six electronic databases were systematically searched from inception to May 2017, using a strategy that included multiple terms for RCTs, cancer, mind‐body medicine, and FCR. Data extraction and reporting followed Cochrane and Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) guidelines. Pooled effect sizes on self‐report measures of FCR were computed by using random‐effects models. Results: Nineteen RCTs (pooled N = 2806) were included. Most studies (53%) were published since 2015 and targeted a single cancer type (84%; mostly breast). Intervention sessions (median = 6, mode = 4) tended to last 120 minutes and occur across 1.5 months. Delivery was predominantly in‐person (63%) to either groups (42%) or individuals (42%). Most interventions incorporated multiple mind‐body components (53%), commonly cognitive‐behavioral skills (58%), or meditative practices (53%). Small‐to‐medium pooled effect sizes were observed postintervention (Hedges' g = −0.36, 95% CI = −0.49, −0.23, P < .001) and at follow‐up assessments (median = 8 months, P < .001). Potential modifiers (control group design, group/individual delivery, use of cognitive‐behavioral or mindfulness skills, number of mind‐body components, cancer treatment status, and number of sessions) did not reach statistical significance. Conclusions: Mind‐body interventions are efficacious for reducing FCR, with small‐to‐medium effect sizes that persist after intervention delivery ends. Recommendations include testing effects among survivors of various cancers and exploring the optimal integration of mind‐body practices for managing fundamental uncertainties and fears during cancer survivorship.